Comment on Ng's "Wealth Redistribution, Race & Southern Public Schools, 1880-1910" - Sherman Dorn (Arizona State University, 2001)
Wherein the author raises criticisms and advances qualifications to the conclusions reached by Kenneth Ng is his article "Wealth Redistribution, Race and Southern Public Schools, 1880-1910.